Motivating public sector employees: Evidence from Greece - K. Koronios; M. Mavromati; A. Kriemadis (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2017)
Purpose: The object of this research is to investigate work motivating factors in the public sector in Greece, as well as to study demographic attributes, placing emphasis on age and gender as determinants of employee motives. Design/methodology/approach: To answer our research questions, a questionnaire was distributed at the beginning of 2015 to a public-sector organization in central Greece. A total of 318 anonymous survey responses were collected and analysed with SPSS. Findings: In the public organization under survey, the leading employee motives are an increase in salaries, opportunities for hierarchical advancement in the organization, as well as the development of personal skills. Moreover, motivational differences are noted among Baby Boomers, Generation X and Generation Y. Research limitations/implications: As the present study has been conducted on a single public organization, awareness should be raised as far as the generalizability of the results providing useful insights for further exploration. Originality/value: Limited research has been conducted in the Greek public sector comparing motives among generations.
Keywords: M12; M54; O15; 330; Motivation; Generations; Public Sector; Greece